Inequality among European Working Households, 1890-1960 - Ian Gazeley; Rose Holmes; Andrew T. Newell; Kevin Reynolds; Hector Gutierrez Rufrancos (Institute of Labor Economics (IZA), 2018)
In this article we map, for the first time, the time-path of the size distribution of income among working class households in Western Europe, 1890-1960. To do this we exploit data extracted from a large number of newly digitised household expenditure surveys. Many are not representative of the population, or even of their target-subpopulation, as methods of social investigation were initially primitive, though rapidly evolving over this period. We overcome the consequent problem of comparability by exploiting our knowledge of the methods used by early social investigators to estimate of the scale of known biases. For some we have the original household data, but in most cases we have tables by income group. One by-product of this work is an evaluation of the range of estimation methods for distributional statistics from these historical tables of grouped data. Our central finding is that inequality among working households does not follow the general downward trend in inequality for the early part of the century found in labour share and top income studies. Contrary to Kuznets' prediction, our evidence suggests that on average income inequality among European working households remained stable for three generations from the late nineteenth century onwards.
Keywords: N33; N34; O15; 330; inequality; working households; Europe; 20th century